2020
DOI: 10.1145/3380973
|View full text |Cite
|
Sign up to set email alerts
|

MapLUR

Abstract: Land-use regression (LUR) models are important for the assessment of air pollution concentrations in areas without measurement stations. While many such models exist, they often use manually constructed features based on restricted, locally available data. Thus, they are typically hard to reproduce and challenging to adapt to areas beyond those they have been developed for. In this article, we advocate a paradigm shift for LUR models: We propose the D ata-driven, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Indeed, spatial features, such as topography, proximity to infrastructure as well as the land use in a buffer area near to air quality monitoring stations, have proven to improve the performance of deep learning-based air pollution predictions [49]. DNN LUR, such as [50] provide an approach of geo-context in an unsupervised way that outperforms other approaches such as RF. For these reasons, spatial error prediction will require the use of either Bayesian DNN or Deep Ensemble.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, spatial features, such as topography, proximity to infrastructure as well as the land use in a buffer area near to air quality monitoring stations, have proven to improve the performance of deep learning-based air pollution predictions [49]. DNN LUR, such as [50] provide an approach of geo-context in an unsupervised way that outperforms other approaches such as RF. For these reasons, spatial error prediction will require the use of either Bayesian DNN or Deep Ensemble.…”
Section: Discussionmentioning
confidence: 99%
“…This means that during the backpropagation process, only the paths that increase the activation of a particular feature or neuron are considered, and paths that reduce the activation are effectively ignored. Steininger et al (2020) used guided backpropagation to visualize the regions of an input image that a neural network is focusing on for NO2 estimation, allowing visualization of which parts of the image the model is paying attention to. This helps in understanding what aspects of the input data have the most influence on the network's decision.…”
Section: Guided Backpropagation (Gb)mentioning
confidence: 99%
“…Only Steininger et al (2020) employed satellite images for air pollution prediction. They used guided backpropagation (GB) as a model-specific method and found that the model prioritizes motorways, trunk roads, and primary roads in map images to predict NO2 concentration.…”
Section: Limitations Of the Evidence Included In The Reviewmentioning
confidence: 99%
“…Due to the individual differences in daily activities, each person has very individual exposure patterns, which obviously cannot be adequately captured by measurements at a few monitoring stations in the city (improved approach; see Steininger et al 2020) but require person-specific measurements (Dias and Tchepel 2018;Hinwood et al 2007). However, air pollution data from a terrestrial monitoring station can only be considered representative of the surrounding district.…”
Section: Measuring Environmental Stressorsmentioning
confidence: 99%